2017
DOI: 10.3892/mmr.2017.7818
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic differentiation of mouse bone marrow-derived mesenchymal stem cells using a novel 3D culture system

Abstract: The development of novel culture systems that mimic the in vivo microenvironment may be beneficial for inducing the differentiation of stem cells and promoting liver function. In the present study, spheroid cultures and decellularized liver scaffolds (DLSs) were utilized to obtain differentiated hepatocyte-like cells. Mouse bone marrow (BM)-derived mesenchymal stem cells (MSCs) self-aggregated into spheroids under low-attachment conditions and implanted into the DLSs via a negative pressure suction device. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In fact, cells show different physiological and morphological results in two-dimensional (2D) and 3D environments [10]. In particular, MSCs have better osteogenic [11], adipogenic [12], and hepatic [13, 14] differentiation behavior in the 3D environment. Moreover, MSCs show improved differentiation when they are co-cultured with other types of cells such as human umbilical vein endothelial cells (HUVECs) [15], osteoblasts [16], and hematopoietic stem/progenitor cells (HSPCs) [17] compared with those cultured alone in the 3D environment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, cells show different physiological and morphological results in two-dimensional (2D) and 3D environments [10]. In particular, MSCs have better osteogenic [11], adipogenic [12], and hepatic [13, 14] differentiation behavior in the 3D environment. Moreover, MSCs show improved differentiation when they are co-cultured with other types of cells such as human umbilical vein endothelial cells (HUVECs) [15], osteoblasts [16], and hematopoietic stem/progenitor cells (HSPCs) [17] compared with those cultured alone in the 3D environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cells of mesodermal origin (osteoblasts, chondroblasts, and adipocytes), MSCs are capable of generating neural cells, hepatocytes, alveolar epithelial cells, insulinproducing cells, cardiomyocytes, indicating their clinical application (7)(8)(9)(10)(11)(12)(13)(14). Several lines of evidence suggested that MSCs have capacity to differentiate into functional cardiomyocytes (9), hepatocytes (10,11), alveolar epithelial cells and lung precursor cells (13) contributing to the regeneration of injured myocardium, liver and lungs (12,(15)(16)(17). Additionally, in paracrine manner, through the production of immunomodulatory factors (indoleamine 2,3-dioxygenase (IDO), prostaglandin E2 (PGE2), nitric oxide (NO), transforming growth factor beta (TGF-β), interleukin (IL)-10, interleukin 1 receptor antagonist (IL-1Ra) and growth related oncogene (GRO), MSCs are able to suppress detrimental autoimmune response and to attenuate autoimmune and chronic, inflammatory diseases (3,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells are shown to play an important role in hepatic differentiation . During hepatic differentiation, there were significant changes in the expression of miRNAs in MSCs . We further investigated whether our observations described above hold true in human primary cells.…”
Section: Discussionmentioning
confidence: 87%
“…33 During hepatic differentiation, there were significant changes in the expression of miRNAs in MSCs. 34,35 We further investigated whether our observations described above hold true in human primary cells. Chronic liver diseases are characterized by high levels of circulating cytokines and growth factors, such as interferon-γ, IL-10, IL-4, IL-2, HGF, EGF, and TNF-α.…”
Section: Discussionmentioning
confidence: 94%